COPING WITH THE CHALLENGES OF TEACHING ENGLISH FOR SPECIFIC PURPOSES TO ADULT LEARNERS - Dwi Mawan Karifianto (Universitas Muhammadiyah Gresik, 2015)
The paper is aimed at understanding the notion of English for Specific Purposes(ESP) commonly taught to adult learners. ESP is different from general English in the waythat it is taught to meet students' specific needs or taught to learners of specific disciplines;thus, it has its special features. In addition, teaching English to adult learners presentsseveral challenges that are different from other age group of learners. English teachers needto understand the characteristics of adult learners so that they can take that intoconsideration in order to increase the effectiveness of their instruction. This paperdiscusses both issues—ESP and adult learners—and the practical implications that theybring to the English language teaching context that teachers of ESP need to know.